POTENTIAL OF SILVER ECONOMY IN THE EUROPEAN UNION (SELECTED VIEWS) - Pauhofova, Iveta; Dovalova, Gabriela (European Scientific Journal, ESJ, 2015)
This paper deals with the assumptions of realization of silver economy in the EU, regarding expected effects related to aging in Europe. Intention is to present differences in size of potential demand formation of population in old and new EU countries. We also examine differences in consumption on EU level as well as in consumption of households in a given age groups. Special attention is paid to Slovakia and main consumption constraints including income inequality in particular regions and among them. The supplemented aspects of technological changes and determinants of consumption with both economical and non-economical character are included. For potential demand analysis we used EU-SILC data and individual data from Social Insurance Agency in Slovakia. In crisis period, problems with economic growth and high level of unemployment rate together with stagnation of wages represent barriers for formation of potential demand. These factors could significantly entail lower levels of average pensions, which could be accompanied with changing consumer preferences, purchasing power, aggregate demand, employment and sectors of production. At the end of the paper we conclude that in the new EU member states there is only little space for real saturation of consumption by goods and services for older people in terms of the concept of silver economy. On the other hand, Germany, Austria, France, Mediterranean, Nordic and Benelux countries represent a significant consumer opportunity in terms of the potential demand of older people aged 50 years and over.